Porphyrin- or phthalocyanine-bridged silsesquioxane nanoparticles for two-photon photodynamic therapy or photoacoustic imaging. Issue 43 (30th October 2017) - Mauriello-Jimenez, Chiara; Henry, Maxime; Aggad, Dina; Raehm, Laurence; Cattoën, Xavier; Wong Chi Man, Michel; Charnay, Clarence; Alpugan, Serkan; Ahsen, Vefa; Tarakci, Deniz Kutlu; Maillard, Philippe; Maynadier, Marie; et al.
Abstract : Porphyrin- or phthalocyanine-bridged silsesquioxane nanoparticles (BSPOR and BSPHT) were prepared. Abstract : Porphyrin- or phthalocyanine-bridged silsesquioxane nanoparticles (BSPOR and BSPHT) were prepared. Their endocytosis in MCF-7 cancer cells was shown with two-photon excited fluorescence (TPEF) imaging. With two-photon excited photodynamic therapy (TPE-PDT), BSPOR was more phototoxic than BSPHT, which in contrast displayed a very high signal for photoacoustic imaging in mice.